Increased Fatigability in Women With Persistent Cancer-Related Fatigue After Breast Cancer Treatment: A Pilot Study. Issue 3 (28th July 2022) - Wood Magee, Lisa J.; Kneiss, Janet; Wechsler, Stephen; Singh, Ayesha Bani; Fox, Annie B.; Peppercorn, Jeffrey; Pirl, William F.
Abstract : Purpose: To examine whether survivors of breast cancer (SBC) with persistent cancer-related fatigue (CRF) have greater fatigability than their nonfatigued counterparts. Methods: Measures of fatigability, including endurance, perceived exertion, lower extremity muscle force and power, and sit-to-stand time (STST), were assessed in 43 women (21 with persistent CRF) after a sit-to-stand fatigue (STSF) task. Group differences in fatigability outcomes were examined using analysis of variance. Results: SBC with persistent CRF had lower endurance ( P = .003, ηp 2 = 0.205) and reported greater perceived exertion ( P < .001, ηp 2 = 0.284) during the STSF task, and demonstrated lower postexertional force ( P = .035, ηp 2 = 0.109), power ( P = .001, ηp 2 = 0.242), and slower STST ( P = .001, ηp 2 = 0.258) compared with SBC without CRF. Conclusions: SBC with persistent CRF have increased fatigability compared with those without CRF. Our findings suggest that exercise recommendations for women with persistent CRF after breast cancer treatment should include activities that increase lower limb muscle force and power, such as heavy resistance or explosive-type strength training.